Principles of Compliance and Conversation Implications in the Sultan's Event at SCTV Television Station March 2021 Edition (Pragmatic Approach) - Dewi Asmarita; Yenny Puspita; Siti Rukiyah (Budapest International Research and Critics University, 2021)
This study discusses the principle of politeness and conversational implicatures in The Sultan program on the March 2021 edition of SCTV television station (pragmatic approach). The problem in this research is how are the principles of politeness and conversational implicatures in the program The Sultan on the March 2021 edition of SCTV television station (pragmatic approach). The purpose of this study is to find out how the principle of politeness and conversational implicatures in the program The Sultan on the March 2021 edition of SCTV television station (pragmatic approach). The method used in this research is the postpositivism paradigm method to develop qualitative research methods. The source of the data in this research is the program The Sultan which is on the SCTV television station. Data collection techniques used are listening techniques and note-taking techniques. Based on the results of research and discussion, it can be concluded that the most common in the politeness principle are 13 maxims of compatibility, while in conversational implicatures there are 13 scaled implicatures.